GE_GERICHTE C/10611/2009 vom 19. Juni 2015 - GE Cour de justice (2015)
PRIX DE L'OUVRAGE; DÉPENS; GARANTIE EN RAISON DES DÉFAUTS DE LA CHOSE; OUVRAGE(CONTRAT D'ENTREPRISE); SUREXPERTISE; EXPERTISE | CO.368; CO.373.1; aLPC.267